Power Move: um caminho dançante para o movimento - ROSÁRIO, Renan Santos do (2018)
This course conclusion work is grounded in goals describe six basic movements of the subgenre of dance move called breakin power moves, as well as establishing relations theoretical and philosophical about dance and body conceptions that guided my way through the experiences and relationships established moves towards the movement power. Therefore, dialogue with Hoffman and Harris (2002) in their study of kinesiology, Marleu Ponty (2006) and phenomenology, as well as Bolsanello (2005) for the notion of body experience while. This approach seeks to collaborate with the art scene belenense in its production of knowledge through dance.